Murray & Nadel's textbook of respiratory medicine - Broaddus, V. Courtney; Mason, Robert J.; Ernst, Joel D.; King, Talmadge E., Jr; Lazarus, Stephen C.; Murray, John F. 1927-2020; Nadel, Jay A., 1929-; Slutsky, Arthur S. 1948-; Gotway, Michael B. (Elsevier/Saunders, 2016)
Ideal for fellows and practicing pulmonologists who need an authoritative, comprehensive reference on all aspects of pulmonary medicine, Murray and Nadel's Textbook of Respiratory Medicine offers the most definitive content on basic science, diagnosis, evaluation and treatment of the full spectrum of respiratory diseases.- Resumé vydavatel
Preceded by: Murray and Nadel's textbook of respiratory medicine. 5th ed. / editors, Robert J. Mason ... [et al.]. c2010.
Keywords: nemoci dýchacích cest; airways diseases; elektronické knihy; učebnice; electronic books; textbooks